Portfolio optimization of safety measures for reducing risks in nuclear systems. (November 2017) - Mancuso, A.; Compare, M.; Salo, A.; Zio, E.
Highlights: Risk-based optimization to select safety measures in high-risk installations. Computationally viable algorithm to identify cost-efficient portfolios. Feasibility of the approach shown by revisiting an earlier case study concerning an airlock system. Comparison of the results with the procedure on risk importance measures. Abstract: In the framework of Probabilistic Risk Assessment (PRA), we develop a method to support the selection of cost-effective portfolios of safety measures. This method provides a systemic approach to determining the optimal portfolio of safety measures that minimizes the risk of the system and thus provides an alternative to using risk importance measures for guiding the selection of safety measures. We represent combinations of events leading to system failure with Bayesian Belief Networks (BBNs) which can be derived from traditional Fault Trees (FTs) and are capable of encoding event dependencies and multi-state failure behaviours. We also develop a computationally efficient enumeration algorithm to identify which combinations (portfolios) of safety measures minimize the risk of failure at different costs of implementing the safety measures. The method is illustrated by revisiting an earlier case study concerning the airlock system of a CANDU Nuclear Power Plant (NPP). The comparison of results with those of choosing safety measures based on risk importance measures shows that our approach leads to considerably lower residual risk at different cost levels.